Application of Importance Performance Analysis Method in Measuring the Level of Community Satisfaction with the Quality of Service of the Minasa Upa Public Health Center - Muchlis, Resti Wulandari; Saleh, Anis; Hafid, Muhammad Fachry (Omnia Tempus, 2022)
Purpose: The purpose of this study was to measure the level of patient satisfaction with service quality at the Minasa Upa Health Center. Design/methodology/approach: This study uses the Importance Performance Analysis (IPA) method to measure community satisfaction with service quality. Data was obtained by distributing questionnaires. Five dimensions are measured: tangible variables, reliability, responsiveness, assurance, and empathy. Findings: The results of this study indicate that the quality of service at the Minasa Upa Public Health Center in terms of five dimensions results in a perception value below the expected value. These results suggest that patient satisfaction with services at the Minasa Upa Health Center in Makassar city still needs to be fulfilled. Research limitations/implications: This research was fieldwork at the Minasa Upa Public Health Center. The respondents in this study were people who had visited or received treatment at the Minasa Upa Public Health Center, as many as 100. Originality/value: Public Health Center describes a public service engaged in health services that has an essential role in the National Health System. Public Health Center is a health service provider organization that exists in all regions. The quality of service at the Minasa Upa Public Health Center is still not good, as evidenced by the perceived value, which is still below the expected value and has led to decreased public confidence in seeking treatment at the health center. So, this can affect the decline in health levels in the community. In addition to this, facilities and infrastructure factors still do not satisfy service users.